KEPASTIAN HUKUM DAN PERLINDUNGAN HAK PEMILIK TANAH DALAM PEMBATALAN AKTA JUAL BELI OLEH PENGADILAN - Akbar Firman Syah; Miko Aditiya Suharto (Jurnal Ilmiah Advokasi, 2026)
The annulment of a Sale and Purchase Deed (Akta Jual Beli/AJB) by the court, despite being executed in accordance with legal procedures, creates legal uncertainty for good-faith purchasers in land transactions. This study aims to analyze the application of the principle of legal certainty in Decision Number 31/Pdt.G/2024/PN Bangil and to examine the forms of legal protection available for good-faith buyers. The novelty of this research lies in its analysis of the judiciary’s tendency toward formalistic reasoning in assessing the validity of AJBs, which consequently weakens substantive legal protection for purchasers acting in good faith. This study employs a normative legal research method using statutory, conceptual, and case approaches through qualitative-prescriptive analysis of primary, secondary, and tertiary legal materials. The findings reveal that the panel of judges placed greater emphasis on formal aspects, particularly the delay in the land title transfer registration process, rather than protecting purchasers who had fulfilled the legal requirements of a valid transaction in good faith. This condition demonstrates that the application of substantive legal certainty in land dispute resolution remains inadequate. Legal protection for good-faith purchasers can be strengthened through the optimization of the Land Deed Official’s (PPAT) role, timely land registration obligations, and the availability of repressive legal remedies such as appeals, cassation, judicial review, and derden verzet. This study underscores the importance of reconstructing legal protection for good-faith purchasers in order to achieve a balance between formal legal certainty and substantive legal certainty, while also serving as a reference for the development of land law policies and technical guidelines for judges and PPAT officials.Keywords: Legal Certainty; Legal Protection; Good-Faith Purchaser; Sale and Purchase Deed.